Plasma lipidomics of monozygotic twins discordant for multiple sclerosis. Issue 12 (7th November 2020) - Penkert, Horst; Lauber, Chris; Gerl, Mathias J.; Klose, Christian; Damm, Markus; Fitzner, Dirk; Flierl‐Hecht, Andrea; Kümpfel, Tania; Kerschensteiner, Martin; Hohlfeld, Reinhard; Gerdes, Lisa A.; Simons, Mikael
Abstract: Blood biomarkers of multiple sclerosis (MS) can provide a better understanding of pathophysiology and enable disease monitoring. Here, we performed quantitative shotgun lipidomics on the plasma of a unique cohort of 73 monozygotic twins discordant for MS. We analyzed 243 lipid species, evaluated lipid features such as fatty acyl chain length and number of acyl chain double bonds, and detected phospholipids that were significantly altered in the plasma of co‐twins with MS compared to their non‐affected siblings. Strikingly, changes were most prominent in ether phosphatidylethanolamines and ether phosphatidylcholines, suggesting a role for altered lipid signaling in the disease.